Математична модель пластини з подвійною модуляцією діелектричної проникності - Гоблик, В.В.; Ничай, І.В. (Моделювання та інформаційні технології, 2009)
A mathematical model, as a branched continual fraction, of periodically nonuniform dielectric plate, is considered. The numerical results of spatial distribution of the field for the different values of period of the followings of nonuniformities are got. The features of the field distribution which arise up as a result of modulation of dielectric conductivity of structure by the two periodic sequences of rectangular functions are analysed.